Genetic Detection for Staphylococcus aureus bacterialin Urinary Tract Infection cases in Hilla City - Ali Kadhim Aljarah (Journal of Global Pharma Technology, 2018)
Fourteen urine Specimens were collected of patient with Different Ages & gender that had been infected with the UTI that previously Diagnosed in Hilla Educational Hospital in period from Feb. 2016 to Mar. 2016 for detection of Bacterial causative agent that cause the UTI , samples were transferred directly to laboratory then centrifuged in ( 3000 rpm ) for 15 min., taking pellet for bacterial culturing on mannitol salt agar in 37C° for 24 hr. in aerobic conditions changing the media to yellow color as an indicator for growth of S.aureusthen followed by DNA isolation from bacteria for further genetic detection by PCR, selecting ( mec A1 gene ) as an indicator gene that related to the virulence factors in the S.aureus, agarose gel electrophoresis for mec A1 primer amplification showed 32 positive result indicated to the presence of this bacteria as one of most causative bacterial pathogenic agent in UTI, these rapid definitive diagnosis is useful for further treatment by selection the determined antibiotic drug latterly.Keywords: Mec A gene, Staphylococcus aureus, UTI, PCR